MicroRNA as therapeutic targets for treatment of depression - Hansen, Katelin F (Dove Medical Press, 2013)
Depression is a potentially life-threatening mental disorder affecting approximately 300 million people worldwide. Despite much effort, the molecular underpinnings of clinical depression remain poorly defined, and current treatments carry limited therapeutic efficacy and potentially burdensome side effects. Recently, small noncoding RNA molecules known as microRNA (miRNA) have gained prominence as a target for therapeutic intervention, given their capacity to regulate neuronal physiology. Further, mounting evidence suggests a prominent role for miRNA in depressive molecular signaling. Recent studies have demonstrated that dysregulation of miRNA expression occurs in animal models of depression, and in the post-mortem tissue of clinically depressed patients. Investigations into depression-associated miRNA disruption reveals dramatic effects on downstream targets, many of which are thought to contribute to depressive symptoms. Furthermore, selective serotonin reuptake inhibitors, as well as other antidepressant drugs, have the capacity to reverse aberrant depressive miRNA expression and their downstream targets. Given the powerful effects that miRNA have on the central nervous system transcriptome, and the aforementioned studies, there is a compelling rationale to begin to assess the potential contribution of miRNA to depressive etiology. Here, we review the molecular biology of miRNA, our current understanding of miRNA in relation to clinical depression, and the utility of targeting miRNA for antidepressant treatment.